Association between rs1049174 NKG2D gene polymorphism and idiopathic recurrent spontaneous abortion in Iranian women: a case-control study. (4th July 2021) - Abdian Asl, Amir; Vaziri Nezamdoust, Fereshteh; Fesahat, Farzaneh; Astani, Akram; Barati, Meisam; Raee, Pourya; Asadi-Saghandi, Abolghasem
Abstract: Natural killer group 2, member D ( NKG2D ) is one of the best known activating receptors of NK cells, which recognises its ligand on altered or stressed cells and activates NK cells to kill them. In this study, the single nucleotide polymorphism of the NKG2D gene for rs1049174 mutation was compared in 140 women with recurrent spontaneous abortion (RSA) and 175 control women with at least one successful pregnancy and without any known pregnancy loss. The findings just revealed that GG genotype and G allele were significantly higher in the case group compared with the control group ( p < .001). Our results regarding decreased risk of RSA in C allele (OR = 0.438; 95%CI = 0.310–0.619; p < .001), and GC genotype (OR = 0.492; 95%CI = 0.214–0.574; p < .001) compared with G allele and GG genotype respectively. This study demonstrated a significant association between NKG2D gene polymorphism (rs1049174 G/C) and the risk of RSA in Iranian women. Impact statement: What is already known on this subject? According to previous investigations, maternal immune responses may affect the foetus, causing recurrent spontaneous abortion (RSA). The main cause of RSA has not yet been detected in nearly 50% of the cases. What do the results of this study add? The results showed that the frequency of G allele and C allele were significantly different in the case group and control group. What are the implications of these findings for clinical practice and/or further research? The results suggest a protective function of C allele because it significantly decreased the risk of RSA compared to G allele. It improves inhibition of NK cells and probably participates in maintaining pregnancy in fertile controls; whereas, G allele is related to a slight inhibition of NK cells, probably leading to increase effectiveness of NK activation and undesirable inflammation, which consequently causes foetal rejection.